The Effect of the Modeling the Way Method in Improving Students' Speech Skills at SMA Swasta Nurul Iman Tanjung Morawa - Rita Sari Sitepu; Nurhayati; Diah Kusyani (International Journal of Educational Research Excellence (IJERE), 2023)
This study aims to determine the effect of the modeling the way method in improving the speech skills of Nurul Iman Tanjung Morawa High School students in the 2021-2022 Academic Year. This study uses a quantitative approach in an effort to test the hypotheses that have been prepared. The location of the research being conducted was at Nurul Iman Tanjung Morawa High School in the 2021-2022 Academic Year. The reason for taking this research location is because the population is sufficient, this location is easily accessible by public transportation and not far from the researcher's residence so that it can save time, effort and money. Based on the review carried out, it was obtained data that all class XI students of Private High School Nurul Iman Tanjung Morawa for the 2021-2022 Academic Year totaled 98 people. Based on the results of the research and discussion it can be concluded that in general the speech skills of class XI SMA Nurul Iman Tanjung Morawa before the modeling the way method was applied to composing speeches in Indonesian were categorized as low. The average score of the students' posttest showed a result of 87.96 which was above the KKM score with the percentage of completeness criteria composing student speeches that had completed learning by 91% and those that had not been completed by 9%, so learning by applying the modeling the way method was declared successful because the number students who score above the KKM above 45%.